Heroism as a Global Phenomenon in Contemporary Culture - Korte, Barbara; Wendt, Simon; Falkenhayner, Nicole (Routledge Studies in Cultural History, 2019)
Heroes and heroic discourse have gained new visibility in the twenty-first century. This is noted in recent research on the heroic, but it has been largely ignored that heroism is increasingly a global phenomenon both in terms of production and consumption. This edited collection aims to bridge this research void and brings together case studies by scholars from different parts of the world and diverse fields. They explore how transnational and transcultural processes of translation and adaptation shape notions of the heroic in non-Western and Western cultures alike. The book provides fresh perspectives on heroism studies and offers a new angle for global and postcolonial studies.